The association of body mass index and gestational diabetes with preeclampsia a hospital-based case-control study in Malaysia - Zainal Abidin Bin Abu Bakar
This hospital-base case-control study was conducted 1) to determine the antenatal characteristics of mothers with preeclampsia in Hospital Ipoh, Perak from January 1998 to December 1998, namely sociodemographic factors, present pregnancy history, antenatal care, previous obstetric history, past medical history, social history and family history; and 2) to determine if there is an independent association between preeclampsia and the following factors: body mass index and gestational diabetes. The study subjects included 232 records of cases of preeclampsia and 464 controls recruited from those who consulted at the Obstetrics and Gynaecology department in Hospital Ipoh, Perak.The results of the logistic regression analysis showed that maternal weight gain modified the effect of high body mass index on preeclampsia. Among pregnant women who gained weight less than 9 kg in the entire pregnancy, those who were obese or overweight had 2.99 (95CI=1.13-7.91) greater likelihood of developing preeclampsia compared to their couterparts who were normal weight or underweight. Among pregnant women whose weight gain was at least 9 kg in the entire pregnancy, high body mass index was protective with adjusted odds ratio of 0.36 (95CI=0.09-1.45). However, this protective association could readily be explained by chance (p-value=0.1499). The effect of the interaction between body mass index and weight gain on preeclampsia could have been affected by the methodological issues described in the discussion section.For the association between gestational diabetes and preeclampsia, pregnant women who had gestational diabetes had 2.64 times greater likelihood of developing preeclampsia than those without gestational diabetes. The risk was statistically significant (p=0.020; 95CI=1.17-5.98).Based on these findings, the importance of preconception counseling of obese women regarding the adverse effects of obesity in pregnancy is deemed necessary. Preconception counseling to any married couple especially in this high-risk individual in essential in promoting healthy life. To do so, a prepregnancy counseling clinic has to be set up and the community should be informed of its existence. Collaborative and co-operative efforts between the Division of Religious Affairs and Ministry of Health is essential so that a module for pre-marital courses can be formulated and taught to all couples who intend to get married.Future studies should be consider the role of other potential confounders such as calcium or fish intake, physical activity and job stress during pregnancy, barrier methods and paternal change in elucidating the causation of preeclampsia among pregnant women. These risk factors should also be examined in a cohort study and should include both nulliparas and multiparas with their risks separately determined. Futhermore, to determine the dose-response relationship between body mass index and preeclampsia, this risk factor should be separated for the overweight and obese women and gestational age has to be controlled.It would also be of interest to evaluate body fat distribution in association with preeclampsia, since persons with a preponderance of abdominal fat deposition tend to be insulin resistant and have several metabolic abnormalities.